Clinical and Genetic Features of a Large Monocentric Series of Familial Non-Medullary Thyroid Cancers - Cirello, Valentina; Colombo, Carla; Karapanou, Olga; Pogliaghi, Gabriele; Persani, Luca; Fugazzola, Laura (Frontiers in Endocrinology, 2021)
Several low penetration susceptibility risk loci or genes have been proposed in recent years with a possible causative role for familial non-medullary thyroid cancer (FNMTC), though the results are still not conclusive or reliable. Among all the candidates, here fully reviewed, a new extremely rare germline variant c.3607A>G (p.Y1203H) of the DUOX2 gene, has been recently reported to co-segregate with the affected members of one non-syndromic FNMTC family. We aimed to validate this finding in our series of 33 unrelated FNMTC Italian families, previously found to be negative for two susceptibility germline variants in the HABP2 and MAP2K5 genes. Unfortunately, the DUOX2 p.Y1203H variant was not found in either the 74 affected or the 12 not affected family members of our series. We obtained interesting data by comparing the clinico-pathological data of the affected members of our kindreds with a large consecutive series of sporadic cases, followed at our site. We found that familial tumors had a statistically significant more aggressive presentation at diagnosis, though not resulting in a worst outcome. In conclusion, we report genetic and clinical data in a large series of FNMTC kindreds. Our families are negative for variants reported as likely causative, namely those lying in the HABP2, MAP2K5 and DUOX2 genes. The extensive review of the current knowledge on the genetic risk factors for non-syndromic FNMTCs underlies how the management of these tumors remains mainly clinical. Despite the more aggressive presentation of familial cases, an appropriate treatment leads to an outcome similar to that observed for sporadic cases.